Manipulating the Imagination—Enargeia and Persuasion in Augustine’s Confessions and its Classical Roots - Dupont, Anthony (Zeitschrift für antikes Christentum, 2025)
In this article, we discuss examples of Augustine of Hippo's use of the rhetorical technique of enargeia , which strives to make a subject matter mentally visible or evident through vivid narrative descriptions. These examples are found in the anti-Manichaean passages of his Confessions . We posit that illustrative representations of Manichaean doctrine and practice are constructed "before the eyes" ( sub oculos ) of the audience in a way that allows the narrator to elicit and manipulate their emotional response, acquiring their goodwill and inviting them to reject or ridicule the opposing side. We find that enargeia is also used to encourage the audience not only to visualise what is placed before them, but to actualise it into their lives. The aim hereby might be to incite the audience to emulate the path to conversion which stands as a remedy to adhering to Manichaean principles. What’s more, enargeia serves a didactic purpose, whereby counterintuitive concepts are made immediately available through images that express relatable human movements, motivations and emotions. By elucidating aspects of the organic use of enargeia in the Confessions , this article posits a framework within which similar rhetorical strategies in Augustine’s writings, and ancient Christian rhetoric more broadly, might be further explored.